Effect of camel's milk on some histological changes of kidney and liver of male rats treated with cow's livers infected by Fasciola gigantica - الفرطوسي, خالد كاطع (University of Thi-Qar Journal of Science, 2014)
The present study incorporated the effect of milk of camels in histopathological changes in some organs(kidney and liver) of laboratory male rats that treated with cow's livers infected with Fasciola gigantica .The first part have been treated with temperature (100) centigrade while the second did not treat to heating .The treatment of male rats with livers treated and non treated by heat caused histopathological were caused different histopathological symptoms in kidney tissue performed haemorrhage among glomerulouses, necrosis of kidney, absence of glomerulouses, enlargement of space Bowman's capsule, closed, degenerative, hyperpigment and hyperplasia of renal tubules, aggregation inflammatory cells and fibrosis. The results indicated aggregation of inflammatory cells infiltration, degeneration of hepatocytes, enlargement of sinusoids, congestion of the central portal vein, besides fibrosis, edemastatuses. From other hand, the treatment with camel's milk was improved in histopathological changes. While, the severity of histopathological changes was decreased that caused by using of sweating of livers infected, the treatment by camel's milk was highly effective in the improvement the changes and repair the histological damages.